Glutamatergic System in Depression and Its Role in Neuromodulatory Techniques Optimization - Khoodoruth, Mohamed Adil Shah; Estudillo-Guerra, Maria Anayali; Pacheco-Barrios, Kevin; Nyundo, Azan; Chapa-Koloffon, Gina; Ouanes, Sami (Frontiers in Psychiatry, 2022)
Depressive disorders are among the most common psychiatric conditions and contribute to significant morbidity. Even though the use of antidepressants revolutionized the management of depression and had a tremendous positive impact on the patient's outcome, a significant proportion of patients with major depressive disorder (MDD) show no or partial or response even with adequate treatment. Given the limitations of the prevailing monoamine hypothesis-based pharmacotherapy, glutamate and glutamatergic related pathways may offer an alternative and a complementary option for designing novel intervention strategies. Over the past few decades, there has been a growing interest in understanding the neurobiological underpinnings of glutamatergic dysfunctions in the pathogenesis of depressive disorders and the development of new pharmacological and non-pharmacological treatment options. There is a growing body of evidence for the efficacy of neuromodulation techniques, including transcranial magnetic stimulation, transcutaneous direct current stimulation, transcranial alternating current stimulation, and photo-biomodulation on improving connectivity and neuroplasticity associated with depression. This review attempts to revisit the role of glutamatergic neurotransmission in the etiopathogenesis of depressive disorders and review the current neuroimaging, neurophysiological and clinical evidence of these neuromodulation techniques in the pathophysiology and treatment of depression.